The 3‐Year Longitudinal Impact of Sedentary Behavior on the Academic Achievement of Secondary School Students. (12th August 2018) - Hunter, Stephen; Leatherdale, Scott T.; Carson, Valerie
ABSTRACT: BACKGROUND: Sedentary behavior is linked to many adverse health outcomes; however, its relationship with academic achievement is less understood. We examined sedentary behavior's impact on academic achievement over 3 years in 4408 adolescents from the COMPASS study. METHODS: Sedentary behavior (screen‐based: watching/streaming television shows/movies, video/computer games, surfing the internet; communication‐based: texting/messaging/emailing, talking on the phone; and doing homework) and academic achievement (overall math and English marks) were self‐reported. RESULTS: Holding time fixed, moving from the lowest quartile (Q1) to Q2, Q3, or Q4 of watching/streaming television shows/movies (Q2: OR = 0.90; 95%CI: 0.84‐0.97, Q3: OR = 0.85; 95%CI: 0.74‐0.98, Q4: OR = 0.74; 95%CI: 0.64‐0.85) or to Q2 of surfing the internet (Q2: OR = 0.87; 95%CI: 0.78‐0.97) decreased the likelihood of surpassing English standards. Moving from Q1 to Q2 of communication‐based sedentary behavior (OR = 0.90; 95%CI: 0.82‐0.99) decreased the likelihood of surpassing math standards. Moving from Q1 to Q4 (OR = 1.31; 95%CI: 1.15‐1.50) of watching/streaming television shows/movies increased the likelihood of surpassing math standards. Moving from Q1 to Q4 of doing homework (OR = 1.16; 95%CI: 1.02‐1.31) increased the likelihood of surpassing English standards. CONCLUSIONS: Predicting academic achievement from total sedentary behavior is challenging. Targeting specific types of sedentary behavior should be considered for improving math and English achievement.